Investigation of enhanced H2 production from municipal solid waste gasification via artificial neural network with data on tar compounds. (15th February 2023) - Jamro, Imtiaz Ali; Raheem, Abdul; Khoso, Salim; Baloch, Humair Ahmed; Kumar, Akash; Chen, Guanyi; Bhagat, Waheed Ali; Wenga, Terrence; Ma, Wenchao
Abstract: An artificial neural network (ANN) is a biologically inspired computational technique that imitates the behavior and learning process of the human brain. In this study, ANN technique was applied to assess the gasification of municipal solid waste (MSW) with the aim of enhancing the H2 production. The experiments were conducted using a horizontal tube reactor under different parameters: temperatures, MSW loadings, residence times, and equivalence ratios. The input and output variables (released gases) were tested and trained using back-propagation algorithm, and the data distribution by K-fold contrivance. The values of the training (80% data) and validation (20% data) dataset were found satisfactory. The values of regression coefficient (R 2 ) for the training phase were lied between 0.9392 and 0.9991, and 0.9363 and 0.993824 for the testing phase. Whereas; the values of root mean square error (RSME) for the training phase were lied between 0.4111 and 0.8422, and between 0.1476 and 0.7320 for the testing phase. Higher H2 production of 42.1 vol% was produced at the higher reaction temperature of 900 °C with LHV of 11.2 MJ/Nm 3 . According to the tar analysis, the dominant compounds were aromatics (17 compounds) followed by polycyclic aromatic, phenyl, aliphatic, aromatic heterocyclic, polycyclic, and aromatic ketone compounds. Highlights: ANNs model validated the MSW gasification process, successfully. Temperature found as the dominant parameter. H2 production of 42.1 vol% was produced with LHV of 11.2 MJ/Nm 3 . Tar found with aromatic-rich compounds.